(NwOPROSY QZYKA I LITERATURY NARODOW BALKANSKIH STRAN (B:s (NmEVWUZOWSKIJ SBORNIK (B/s - (NdESNICKAQ(B, (NaGNIQ wASILXEWNAs ((Nl(B. :s (Nlgu(B,s, 1986)
(NbIBLIOGR(B. (NW PRIME^(B. (NW KONCE ST(B.s
(Nlgu IM(B. (Na(B.(Na(B. (NvDANOWAs
Keywords: (NqZYKI NARODOW bALKANSKIH STRANs